The Correlation of "Muraqabah" with Mental Health and Physical Health - Masyitoh Chusnan; Andriyani Andriyani; Rohimi Zamzam; Murodi Murodi; Herwina Bahar (Indonesian Journal of Islam and Public Health, 2022)
The Law of the Republic of Indonesia Number 36 of 2009 concerning Health stipulates the definition of health as a healthy condition, both physically, mentally, spiritually and socially that allows everyone to live socially and economically productive. Spiritual health can be in the form of a strong relationship with Allah (taqarrub ilallah), muraqabah, namely the belief that Allah always sees him and feels that Allah is always watching him, his willingness to share and provide benefits for others, strong worship, strong dhikr, and has a strong intention to carry out Allah’s law. In a healthy soul, will be born and a strong body will appear. If someone has a high sense of trust in God, has a very close relationship with God, is easy to receive guidance/guidance, has a very high sense of caring for others, then in this case a strong physique will also be born even though it is possible (physically) at first (considered) weak. Muraqabah is also defined as an earnest effort to live our life and mysticism in the best way through harmony between the content of the heart and appearance under the supervision of Allah SWT, by believing that Allah always sees all human conditions hear and know their words, their circumstances then determine their destiny, and always see the deeds they do and record them. Through murāqabah one watches over their heart (spiritual) and gains an understanding of the heart’s relationship with its creator and its environment.